Characteristics associated with clinical response to Comano thermal spring water balneotherapy in pediatric patients with atopic dermatitis - Davide Geat; Mattia Giovannini; Ezio Gabriele Barlocco; Riccardo Pertile; Stefania Farina; Manuela Pace; Cesare Filippeschi; Giampiero Girolomoni; Mario Cristofolini; Ermanno Baldo (BMC, 2021)
Abstract Background Several studies have investigated the efficacy of balneotherapy in atopic dermatitis (AD), including a pediatric open randomized clinical trial conducted at the Comano thermal spring water center, which showed a significant reduction in AD severity and an improvement of the quality of life. However, so far many studies on balneotherapy in pediatric AD have included relatively small populations without identifying patients' characteristics associated with their response. The aim of the present study was to identify any features associated with the clinical response to the Comano thermal spring water balneotherapy in a large cohort of pediatric AD patients. Methods An observational study was conducted on 867 children aged ≤16 years (females 50.5%, mean patient's age 5.9 years, standard deviation ±3.6 years) with mild to severe AD who underwent balneotherapy at the Comano thermal spring water center (Comano, Trentino, Italy) from April to October 2014. Patients were stratified according to their disease severity, which was evaluated using five SCORing Atopic Dermatitis (SCORAD) categories before and immediately after a thermal spring water balneotherapy course. Potential characteristics associated with the patients' clinical response to Comano thermal spring water balneotherapy were investigated. Results A statistically significant improvement in AD severity was observed after Comano thermal spring water balneotherapy (p < 0.0001). A significantly higher percentage of patients achieving improvement in AD severity was reported among children ≤4 years old (p < 0.0001) with early-onset AD (p < 0.0001), severe AD (p < 0.0001) or coexistent reported food allergies (p < 0.01). The therapy was well tolerated, and no relevant adverse effects were reported during the treatment course. Conclusions Comano thermal spring water balneotherapy is a safe complementary treatment for pediatric patients with AD, as it was able to reduce the disease severity, especially in children ≤4 years old, with early onset AD, severe AD or concomitant food allergies.